Pengaruh Pemberian Pupuk Organik Cair Terhadap Pertumbuhan Dan Hasil Tanaman Cabe Keriting (Capsicum annum L.) - Rini Rahayu Sihmawati; Tiurma Wiliana Susanti P; Wardah (Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to determine the effect of the effectiveness of applying liquid organic fertilizer on the growth and yield of curly chili plants. This study used 3 kinds of liquid organic fertilizer compositions, namely SA (70% vegetable liquid organic fertilizer and 30% animal liquid organic fertilizer) which is not pasteurized and SB (70% vegetable liquid organic fertilizer and 30% animal liquid organic fertilizer) pasteurized. The doses given to plants by spray are SA (2 ml/liter of water), SB1 (2 ml/liter of water) and SB2 (4 ml/liter of water). This study was repeated four times, then the data were analyzed using Anava. If there is a difference, the effect is then tested with a 5% LSD test. Research shows that the use of liquid organic fertilizer that is pasteurized with a concentration of 4 ml/l water (SB2) showed the best results for the height of plant, number of leaves, and number of chilies, while for the number of branches that used the pasteurized liquid fertilizer (SB1 and SB2) showed better results than the liquid fertilizer that is unpasteurized (SA). Keywords : Liquid Organic Fertilizer, Curly Chili